Humor Styles and Personality: A Meta-Analysis of the Relation Between Humor Styles and the Big Five Personality Traits - Mendiburo-Seguel, A (2015)
This research summarizes the knowledge generated in social psychology and positive psychology about the relationship between humor styles, personality and wellbeing. Specifically, a meta-analysis was performed with the results of 15 studies on humor styles measured by the Humor Styles Questionnaire (Martin, Puhlik-Doris, Larsen, Gray & Weir, 2003) in correlation with the personality traits measured by the Big Five Personality model (measured with different scales). Following the steps presented by Rosenthal (1991) for meta-analysis in the case of correlational research, we calculated the total mean r as an indicator of effect size. Results show that affiliative humor has a strong and homogeneous relation to neuroticism and extraversion. The homogeneity and heterogeneity found between variables and possible explanations are discussed in the conclusion. © 2015 Scandinavian Psychological Associations and John Wiley & Sons Ltd.